Un "viaje" por los libros de viajes (Journal of Parents and Teachers, 2014)
The author of this article wants to encourage students and teachers to read travel books. For this purpose, he proposes different activities in which they design and write their own travel books or enjoy reading others'.
Keywords: books; education; travels; journey; reading